1989
DOI: 10.1098/rspb.1989.0047
|View full text |Cite
|
Sign up to set email alerts
|

Properties of acetylcholine-receptor activation in human Duchenne muscular dystrophy myotubes

Abstract: In human myotubes cultured from biopsies of normal subjects and dystrophic patients we investigated, with the patch-clamp technique, the activation properties of the nicotinic acetylcholine receptor (AChoR) in the presence of acetylcholine and suberyldicholine. The single-channel conductance and the lifetime of the openings were not found to differ. In contrast, the average frequency of openings was about four times higher in Duchenne muscular dystrophy (DMD) myotubes in the presence of equal amounts of acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However it has been reported more recently that DMD myotubes express the dystrophin deficiency [66]. Patch-clamp studies of activation properties of the nicotinic acetylcholine receptor in DMD myotubes also revealed that the average frequency of channel openings was about four times higher in DMD myotubes [25]. Patch-clamp studies of activation properties of the nicotinic acetylcholine receptor in DMD myotubes also revealed that the average frequency of channel openings was about four times higher in DMD myotubes [25].…”
Section: D) Duchenne Muscular Dystrophy (Dmd)mentioning
confidence: 97%
“…However it has been reported more recently that DMD myotubes express the dystrophin deficiency [66]. Patch-clamp studies of activation properties of the nicotinic acetylcholine receptor in DMD myotubes also revealed that the average frequency of channel openings was about four times higher in DMD myotubes [25]. Patch-clamp studies of activation properties of the nicotinic acetylcholine receptor in DMD myotubes also revealed that the average frequency of channel openings was about four times higher in DMD myotubes [25].…”
Section: D) Duchenne Muscular Dystrophy (Dmd)mentioning
confidence: 97%